Examining General Education and Special Education Teacher Preparedness for Co-Teaching Students with Disabilities - Causey, Cindy; Soares, Lina; Howerter, Catherine S.; Shannon-Baker, Peggy (Journal of the American Academy of Special Education Professionals, 2022)
It is imperative to understand how teachers are prepared for their role as co-teacher. The purpose of this study was to investigate how general education and special education teachers in one elementary school in Georgia are trained in the instructional practice of co-teaching and their perceptions on how prepared they feel to implement the method. A mixed methods approach was used and included a qualitatively-oriented survey and semi-structured interviews. Data collected in this study revealed that over half of all co-teachers at the elementary school had received some type of training on co-teaching and also felt adequately prepared to serve in the co-teaching role. Overall, participants reported positive perspectives on co-teaching despite there being challenges. The benefits of co-teaching noted a supportive and safe environment, instructional support for students and teachers, and confidence builder due to collaboration. The challenges reported included insufficient time for collaboration, inconsistent teaching schedules, and student behavior problems.